Longitudinal study of quality of life in advanced cancer patients on home parenteral nutrition. (29th May 2017) - Cotogni, Paolo; De Carli, Luca; Passera, Roberto; Amerio, Maria Luisa; Agnello, Elena; Fadda, Maurizio; Ossola, Marta; Monge, Taira; De Francesco, Antonella; Bozzetti, Federico
Abstract: Since there is little knowledge regarding the quality of life (QoL) of cancer patients on home parenteral nutrition (HPN), we planned a prospective, longitudinal, double‐center study to investigate the changes of QoL in these patients. One hundred and eleven adult cancer patients who were candidates for HPN following the indications of the European guidelines were consecutively enrolled. For QoL analysis, EORTC QLQ‐C30 questionnaires were filled at the HPN start and after 1, 2, 3, and 4 months, and scores changes over time were analyzed according to the univariate mixed‐effects linear model for repeated measures. Most patients had gastrointestinal cancers, were severely malnourished, and were in stage IV; two‐thirds were still receiving oncologic treatments. Median weight loss over 3 months and body mass index were 11.7% and 20.7, respectively. Median survival was 4.7 (1–42) months; 67 and 34% of patients survived 3 and 6 months, respectively. Global QoL, physical functioning, role functioning, emotional functioning, appetite loss, and fatigue scores had a statistically significant trend over time ( P  <   0.001, P  <   0.001, P  =   0.007, P  <   0.001, P  =   0.004, P  =   0.022, respectively). At the univariate analyses, the determinants significantly associated with changes in trend over time for physical, role, and emotional functioning were oncologic treatments ( P  <   0.001, P  =   0.014, P  =   0.040, respectively) and for appetite loss they were weight loss and Karnofsky performance status ( P  =   0.003, P  =   0.023, respectively). Global QoL, physical, role, and emotional functioning improved during HPN even in advanced cancer patients on oncologic treatments. Abstract : In this prospective, longitudinal study that included 111 adults advanced cancer patients, global quality of life, physical functioning, role functioning, and emotional functioning had a statistically significant trend over time. At the univariate analyses, the determinants significantly associated with changes in trend over time for physical, role, and emotional functioning were oncologic treatments. Global quality of life improved during home parenteral nutrition even in advanced cancer patients on oncologic treatments.